Factor Principles/Conjunction on Left/Formulation 2

From ProofWiki
Jump to navigation Jump to search

Theorem

$\vdash \left({p \implies q}\right) \implies \left({\left({r \land p}\right) \implies \left ({r \land q}\right)}\right)$


Proof

By the tableau method of natural deduction:

$\vdash \left({p \implies q}\right) \implies \left({\left({r \land p}\right) \implies \left ({r \land q}\right)}\right)$
Line Pool Formula Rule Depends upon Notes
1 1 $p \implies q$ Assumption (None)
2 1 $\left({\left({r \land p}\right) \implies \left ({r \land q}\right)}\right)$ Sequent Introduction 1 Factor Principles: Conjunction on Left: Formulation 1
3 1 $\left({p \implies q}\right) \implies \left({\left({r \land p}\right) \implies \left ({r \land q}\right)}\right)$ Rule of Implication: $\implies \mathcal I$ 1 – 2 Assumption 1 has been discharged

$\blacksquare$


Sources